Evaluation of outcome-based accounting education and training in selected colleges in West Oromia, Ethiopia - Lakew, Deresse Mersha; Musa, Mohammed Getahun (Business, Management and Economics Engineering, 2019)
Purpose: The demand for accountants is increasing from time to time because of the increase in the complexity of the business environment. Higher education institutions are responsible for producing well qualified and ethical accountant required by different organisations. Specifically, Technical and Vocational education and Training (TVET) colleges play a great role in training middle and lower level accountant in Ethiopia. However, academicians, practitioner and employers are raising concern on the excellence and significance of training given in TVET colleges. The objective of this research is to evaluate the education and training in accounting offered by public and private colleges in West Oromia region, Ethiopia.Research Methodology: This study used the cross-sectional survey to obtain the opinion of the trainee, trainers and college deans on how TVET in accounting program is performing about each of the components of CIPP model and identify the knowledge and skill gap as compared to the actual work environment. Both descriptive and inferential statistical tools were used in the analysis.Findings: Examination of the existing TVET in accounting curriculum found that it has a limitation concerning relevance and content. The study further found that there is a lack of sufficient inputs such as an adequate number of qualified trainers, computers and Reference books. Trainers mainly use lecture methods, and there are various problems associated with continuous and summative evaluation. Therefore, it is recommended that the existing curriculum should be revisited, sufficient training inputs should be availed and cooperative training should be strengthened.Research Limitations: This research is based on the respondent’s opinion from a limited part of the country. The nationwide survey is required to conclude at the country level.Practical Implication: the finding and recommendation given in this study can be used in strengthening TVET in accounting education and training in Ethiopia.Originality / Value: Previous studies investigated the challenges of TVET education and training in general terms, and this specific study which focuses on TVET in accounting is the first attempt in Ethiopia.